1985
DOI: 10.1002/joc.3370050607
|View full text |Cite
|
Sign up to set email alerts
|

A comparative performance analysis of three meteorological drought indices

Abstract: Three indices for designating drought are examined and their comparative performance in depicting periods of different drought intensities is discussed. These indices are the rainfall anomaly index (RAI), Bhalme and Mooley drought index (BMDI) and the Palmer drought index (PDI). Using data from Nebraska state as an example, the three indices all appear to be effective in detecting drought periods. The results of the analysis suggest that precipitation is the most important climatic element as an input into met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
3

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(16 citation statements)
references
References 4 publications
0
13
0
3
Order By: Relevance
“…Olukayode Oladipo (1985) found that differences between the RAI and the more complicated indices of the Palmer drought index (Palmer, 1965) and Bhalme and Mooley drought index (Bhalme and Mooley, 1980) were negligible.…”
Section: Rainfall Anomaly Index (Rai)mentioning
confidence: 99%
“…Olukayode Oladipo (1985) found that differences between the RAI and the more complicated indices of the Palmer drought index (Palmer, 1965) and Bhalme and Mooley drought index (Bhalme and Mooley, 1980) were negligible.…”
Section: Rainfall Anomaly Index (Rai)mentioning
confidence: 99%
“…First, it is solely based on precipitation data: SPI time series are obtained through an equiprobability transformation of a cumulative rainfall time series into a standardized normal distribution (McKee et al, 1993). Oladipo (1985) showed that indices based on precipitation can perform well in Nebraska compared with more complex indices such as the PDSI, which has been confirmed over Europe by Lloyd-Hughes and Saunders (2002). Second, it allows drought assessment at different time scales (McKee et al, 1995).…”
mentioning
confidence: 94%
“…Na temelju 73-godišnjeg niza oborina područja Lakoja u Nigeriji, od četiri uspoređene metode, stohastičke komponente vremenskih nizova (SCTS), indeksa anomalije oborina (RAI), indeksa jakosti suše (DSI) i kumulativne informacije o oborinama (CRI) najpogodnijom je ocijenjen indeks anomalije oborina (RAI) jer daje najviše informacija o pojavnosti i jakosti suše analiziranog područja [12]. Usporedba karakteristika triju metoda za ocjenu meteorološke suše, Palmerovog indeksa suše (PDI), Bhalme-Mooley indeksa suše (BMDI) i indeksa anomalije oborina (RAI) za područje Nebraske (SAD) pokazuje da su sve tri metode pogodne za identifikaciju suše, a oborina je dominantan čimbenik pojavnosti suše te su jednostavne metode koje se zasnivaju samo na analizi oborina jednako dobre kao i vrlo složeni indeksi suše [13]. Za područje SAD-a provedena istraživanja pokazuju vrlo veIiku korelaciju (r = 0,97) između indeksa standardiziranih oborina (SPI) i indeksa anomalije oborina (RAI), dok je veza između Palmerovog indeksa jakosti suše (PDSI) i indeksa anomalije oborina znatno slabija [14].…”
Section: Uvodunclassified